Textual Knowledge in Legal Translation - Acuyo-Verdejo, Maria del Carmen (HERMES - Journal of Language and Communication in Business, 2004)
In this paper, we discuss the importance of textual knowledge for the translator in different cultures. By knowing the superstructure of the different text types, the translator will have less difﬁculties in his/her decision-making process. The more familiar the translator is with the different types of texts within a given culture and their super structures, the better the reception of the translated text in the target culture. To this purpose, we have taken as our material texts from industrial property law. Most of the times, the main problem translators encounter derives not only from the subject ﬁeld of a document, where we deal with a very specialised terminology, but also from the text type itself. Recent research in Translation Studies has underlined the importance of this aspect, and speciﬁcally in the ﬁeld of legal translation (Borja, 1998, 2000). This paper is intended to show the speciﬁc textual conventions that characterise some of the most commonly translated documents regarding the registration of a trade mark. The documents considered in this paper make specially reference to those we ﬁnd both in the Spanish and the British legal systems.